Phosphorus-doped graphitic carbon nitride: A metal-free electrocatalyst for quercetin sensing in fruit samples. (10th September 2022) - Kesavan, Ganesh; Vinothkumar, Venkatachalam; Chen, Shen-Ming; Thangadurai, Daniel T.
Highlights: Phosphorous doped graphitic carbon nitride (PgCN) was successfully prepared through a one-step thermal polymerization technique. Influence of P-doping (1, 2, and 3 wt%) on crystal structure, morphology, and electrochemical performance was evaluated. PgCN/GCE with increased phosphorous content effectively enhance the determination of antioxidant quercetin in PBS (pH 3.0). Achieved very low LoD (1 nM) and relevant real sample analysis results enrich the real-world application. Abstract: In this report, phosphorus-doped graphitic carbon nitride (PgCN), a metal-free catalyst, was prepared via a one-step thermal polymerization technique. Additionally, PgCN-x with a different weight ratio of phosphorous doping ( x = 1, 2, and 3 wt %) was successfully synthesized and their structural and morphological properties were evaluated. The developed modified electrodes were engaged for the determination of quercetin (QCN) using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. CV and DPV studies authenticate characteristic peaks ca. at +0.20 and +0.93 V (vs. GCE), respectively. Notably, the improved catalytic activity was perceived for PgCN-3 catalyst, which is 2-fold higher than pristine gCN, was possibly due to high phosphorous content. The quantitative analysis under optimized conditions revealed a comprehensive detection of QCN in the concentration range from 0.025 to 212.2 µM with the lowest detection limit of 1 nM. Interestingly, impedance spectroscopy results disclose a piece of additional evident information to uncover the P-doping by comparing with pristine gCN in the presence of negatively charged redox couple. The currently developed electrochemical method was successfully employed to determine QCN in commercially available fruit juice samples with an acceptable recovery ∼95%. Graphical abstract: Image, graphical abstract